Conformable metal oxide platelets – A smart surface armor for green tribology. (October 2021) - Reinhardt, Hendrik M.; Chizhik, Petr; Dietzel, Dirk; Kim, Hee-Cheol; Dasbach, Michael; Schirmeisen, André; Hampp, Norbert
Abstract: The reduction of friction and wear is a crucial performance criterion for most technical processes. This is particularly true for the ubiquitous case of oil lubricated machinery made from steel components. Here we introduce a facile laser treatment that significantly enhances the tribological performance of bearing steel 100Cr6, a material widely used for the manufacture of ball and roller bearings. By applying repeated nanosecond-pulses of focussed laser-beam irradiation under ambient air, a surface-protective tribo-layer is generated by a method that exploits self-organization for the formation of conformable metal oxide platelets consisting of vertically aligned transition metal oxides nanorods on the steel substrate. These submicron-sized metal oxide platelets protect the surfaces similar to scale armor and the tribological performance of the bearing steel 100Cr6 was significantly enhanced. Based on laboratory tests using a rotational pin-on-disk tribometer under oil lubricated conditions, close to zero wear with simultaneous reduction of friction by 54% was achieved. Even under the harsh conditions in the pin-on-disk tribometer these metal oxide platelets turn out to be remarkably robust against detachment and crumbling for lasting millions of cycles at a slip rate of 100%. The origin of this resilience is based on a special substructure of the platelets that, counter-intuitively for ceramic material, enables shape adaptations to surface deformations emergent upon high mechanical stress. Graphical Abstract: ga1 Highlights: We introduce a facile laser treatment that improves the tribological properties of standard-bearing steel significantly Laser-stimulated self-organization is applied to generate nanostructured metal oxide platelets that protect steel surfaces The metal oxide platelets adapt their shape to plastic deformations of the steel substrate without cracking and crumbling The morphological features of the metal oxide platelets promote the stabilization of lubricant films In a pin-on-disk tribometer the metal oxide platelets are robust against detachment and crumbling for lasting millions of cycles